The Analysis of Student’s difficulties Based on Skemp’s Understanding Theorem at The Grade VII in Quadrilateral Topic - R H Kuncorowati; Mardiyana Mardiyana; D R S Saputro (International Journal of Science and Applied Science: Conference Series, 2017)
In learning process must be found the student’s learning difficulties. The difficulties blocked students in learning process caused by several internal factors(talent, motive, intelligence, motivation) and external factors (family, teachers, peers). The student difficulty in learning general is caused by the lack of understanding of mathematical concepts. Skemp states that there are two types of mathematical concepts understanding, namely instrumental understanding and relational understanding. The purpose of research in this article is to describe the students' difficulties to solve the problem in a quadrilateral topic based on Skemp's Understanding theory. Skemp’s Understanding theory indicators include : students ability to classify objects based on requirements that can build this concept, students ability to apply this concept with algorithm , students ability to giving examples of a concept, students ability to present the concept in mathematics representation, students ability to relating various mathematical concepts, and the ability to develop the necessary terms and conditions is quite a concept. This research was designed in qualitative research. The data was collected by test and interview. The results show that the most difficult is about the students ability to relating various mathematical concepts.